PENGARUH KINERJA TERHADAP KUALITAS PELAYANAN PEGAWAI DINAS PEKERJAAN UMUM PROVINSI SULAWESI TENGAH - Pettalolo, Ilham (Katalogis, 2013)
This research aimed at analyzing the relationship between the personnel’s work ethos, their satisfaction, their dicipline, and their job perfomance. The data were collected through observation reflecting the real condition and interview with 14 respondents representing different level of positions at the provincial general office of Central Sulawesi. The method of research was qualitative analysis in which the data taken from questionnaire were analyzed statistically by using Sperman’s Correlation and Line Analysis Model. It is found that there was a significant influence between the personnel’s work ethos (X1)and their jobperfomance (Y). However, the other variables of the personnel’s job satisfaction (X2) and their dicipline (X3) had indirect influence to the personnel’s job perfomance. These three factors tended to control the personnel’s job perfomance up to 72.99% while other factors outside the model contributed 27.01 % to their job perfomance. Based on the correlation analysis, there were two variables which have positive correlation of 0.507, namely job satisfaction and dicipline. The personnel’s work ethos, however, and job satisfaction have a positively very low correlation of 0.268.